PERAN KELUARGA DALAM PENDIDIKAN - Ahmad Durul Napis (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2017)
Forward the withdrawal of a State determined by previous generations, hence the family as the smallest unit of society has the strategic role in efforts of fostering children's personal and educational. Affection of parents who are sincere and honest to the child it is very useful for survival the next man, would they be useful for others and can scent the surname even to the country. Quality education starts from the family, schools and the environment.